Baseball : a history of America's game - Rader, Benjamin G. (Sport and society., 2018)
In this fourth edition, Benjamin G. Rader updates the text with a portrait of baseball's new order. He charts an on-the-field game transformed by analytics, an influx of Latino and Asian players, and a generation of players groomed for brute power both on the mound and at the plate. He also analyzes the behind-the-scenes revolution that brought in billions of dollars from a synergy of marketing and branding prowess, visionary media development, and fan-friendly ballparks abuzz with nonstop entertainment. The result is an entertaining and comprehensive tour of a game that, whatever its changes, always reflects American society and culture.